2018
DOI: 10.1542/hpeds.2017-0234
|View full text |Cite
|
Sign up to set email alerts
|

Beyond “Asian”: Specific East and Southeast Asian Races or Ethnicities Associated With Jaundice Readmission

Abstract: In this study, we help clarify and move beyond the term "Asian" as a risk factor for readmission due to hyperbilirubinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…One additional context-specific factor was recognized: neonates of Sgaw Karen ethnicity showed an increased risk to develop NH in the first week of life compared to the other ethnic groups. A study in 105 neonates of different Asian ethnicities proposed differences in genes involved in bilirubin metabolism or environmental factors as a possibility for NH readmission [ 39 ]. In this setting, Sgaw Karen have a higher frequency of G6PD deficiency [ 7 ] and analysis of genetic factors involved in bilirubin metabolism is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…One additional context-specific factor was recognized: neonates of Sgaw Karen ethnicity showed an increased risk to develop NH in the first week of life compared to the other ethnic groups. A study in 105 neonates of different Asian ethnicities proposed differences in genes involved in bilirubin metabolism or environmental factors as a possibility for NH readmission [ 39 ]. In this setting, Sgaw Karen have a higher frequency of G6PD deficiency [ 7 ] and analysis of genetic factors involved in bilirubin metabolism is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review has shown that only 45% of hypernatremia cases have jaundice [ 25 ]. The literature has shown increased risk of hyperbilirubinemia among neonates of Asian, both Far East and Southeast Asian descent, and lower propensity among non-Hispanic White infants and African-American infants [ 52 , 53 , 54 ]. The case infant was non-Hispanic White and had minimal elevation of bilirubin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mutations of the UGT1A1 gene are linked to an increased risk of neonatal hyperbilirubinemia in Asian populations, as compared with white populations. In the absence of genetic testing, race or ethnicity is likely a rough approximation of the likelihood of these genetic variations related to hyperbilirubinemia [ 9 , 34 ].…”
Section: Discussionmentioning
confidence: 99%